Electronic defects in lattices of YBa2Cu3O7 and La2 − xSrxCuO4 - Алла Валентиновна Марченко; Павел Павлович Серегин; Валентин Сергеевич Киселев (Physics of Complex Systems, 2022)
Using emission Mössbauer spectroscopy data for the 67Zn isotope and nuclear quadrupole resonance data for the 17O isotope, as well as calculations of the lattice electric field gradient, the effective charges of all atoms in superconducting copper metal oxide YBa2Cu3O7 and La2 – xSrxCuO4 crystal lattices were determined. The effective charges of metal atoms and most oxygen atoms correspond to their standard oxidation states (Y3+, La3+, Ba2+, Sr2+, Cu2+ and O2−). However, the atoms of chain oxygen (in YBa2Cu3O7) and planar oxygen (in YBa2Cu3O7 and La2 – xSrxCuO4) show a reduced charge, which is explained by the localisation of holes in the corresponding sublattices.